Problematika Hak Kekayaan Intelektual sebagai Objek Rahn Tasyjili dalam Perbankan Syariah - Dony Kusuma Madani (International Forum of Researchers and Lecturers, 2025)
Intellectual Property Rights (IPR) have the potential to be recognized as an object of Rahn Tasjily collateral because they meet the criteria of property that can be transferred in accordance with the principles of muamalah in Islamic banking. However, its implementation faces legal challenges, particularly related to the dualism between the provisions of Fiduciary Guarantee (UUJF), which contains potential riba and gharar, and the DSN-MUI Fatwa No. 68/2008, which rejects such non-Sharia elements. This study aims to analyze the position of IPR as marhun according to the principles of muamalah and to identify substantial barriers in its application in Islamic Financial Institutions (LKS), particularly in the aspects of valuation and execution. The method used is normative law with an approach to regulations and concepts, analyzed descriptively and qualitatively using secondary data. The study concludes that the conflict between UUJF and Rahn Tasjily, the high risk of gharar in valuation, and the delays in execution due to the Constitutional Court's decision, highlight the urgent need for OJK and DSN-MUI to issue technical regulations to harmonize and mitigate risks in accordance with Sharia principles.